Meaning of Work and Engagement of INSS Employees in Serving Riverine Communities in the Amazon - Cahú, André D. (Revista del CLAD Reforma y Democracia, 2025)
This article aims to uncover how the experience of INSS employees in serving remote communities in the Amazon, through the PrevBarco program, influences their perceptions of the meaning of work and their engagement with the organization and society. The research, with a qualitative and ethnographic approach, involved 35 days of immersion by the researcher in the program’s activities, using participant observation, field notes, and semi-structured interviews with 22 employees. Discourse analysis of the interviews and content analysis of internal INSS reports were also conducted. The results revealed that the humanized service to vulnerable populations strengthens the employees’ sense of work and engagement. Two new categories also emerged: "work as a driver of synergistic teams" and "transformative connections," which highlight the profound and lasting impact of the PrevBarco experience on employees’ personal and professional lives. The research was limited to the specific context of the Amazon and the perceptions of the participating employees, which may not reflect the entirety of the INSS. The research may contribute to human resource management policies, emphasizing the importance of direct contact between employees and citizens to strengthen engagement. It also contributes to reflections on social inclusion and the reduction of inequalities in access to social security services.